IMPLEMENTASI KEGIATAN DOA REMAJA KATOLIK (REKAT) DI PAROKI SANTO HILARIUS KLEPU - Ag Efendi Darmanto; Don Bosco Karnan Ardijanto (Bahasa Indonesia, 2019)
Prayer was very important in Jesus’ life and the saints’ lives. Prayer also becomes the important need in the faithfuls’ life. Prayer is a mean to fight againts the devil and the power of sin. Prayer is also an expression of faith in God. It also becomes the way of human being to always remember to God. There are some problems: what is prayer? How do the Catholic teens of St. Hilarius’ Parish, Klepu pray together? What kind of benefits of praying together for the Catholic Teens in St. Hilarius’ parish, Klepu? What kind of impedements in praying together that the Catholic Teens of St. Hilarius’ Parish experience? The aims of this research are: to clarify the definition of prayer, to explain how the Catholic Teens of Hilarius’ parish, Klepu to do their praying together, to explain the benefits of prayer together for the Catholic Teens of St. Hilarius’ parish, Klepu. Finally, to identify various factors that supporting or inhibiting the practice of prayer of the Catholic Teens of St. Hilarius’ parish, Klepu. This research used qualitative research methods. In this study there are 10 respondents consisting of 4 male respondents and 6 female respondents. They are between 13-15 years old. They are members of St. Hilarius’ parish, Klepu. The conclusions of the research are: 1) The Catholic Teens of St. Hilarius’ parish, Klepu know the understanding of prayer. 2) The Catholic Teens of St. Hilarius’ parihs, Klepu already carry out prayers in certain times either personally or communal prayer in St. Hilarius’ parish, Klepu. 3) The Catholic Teens of St. Hilarius’ parish, Klepu understand that the benefits of communal prayer are: creating a partnership or relationship with God and friends, as well as the means to develop their personality.